2006
DOI: 10.1381/096089206778026442
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sexual Function in Obese Women Preparing for Bariatric Surgery

Abstract: Obese women complain of significant sexual impairment. Obesity-related sexual dysfunction appears to be a complex condition linked to a range of social, psychological and biological factors. Clinicians are encouraged to evaluate routinely sexual function in this patient population in order to detect those who are in need of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 24 publications
7
50
0
8
Order By: Relevance
“…Women with severe obesity may, in general, have a negative self-and body image, as well as a lower sense of self-esteem when compared to nonobese women. 11,24,26 Thus, the complex interaction between selfperception and self-reported symptoms may inflate the problem of sexual dysfunction attributed to lower urinary tract dysfunction in obese women. Obese women also reported more frequent sexual dysfunction in their spouses with regard to premature ejaculation and erection problems.…”
Section: Discussionmentioning
confidence: 99%
“…Women with severe obesity may, in general, have a negative self-and body image, as well as a lower sense of self-esteem when compared to nonobese women. 11,24,26 Thus, the complex interaction between selfperception and self-reported symptoms may inflate the problem of sexual dysfunction attributed to lower urinary tract dysfunction in obese women. Obese women also reported more frequent sexual dysfunction in their spouses with regard to premature ejaculation and erection problems.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that patients' quality of life, psychological status, body image, and selfesteem have been improved after bariatric surgery (29). In this review two of the studies suggested that depressive symptoms improved in women after bariatric surgery (8,15). We suggest that these changes may affect sexuality positively.…”
Section: Discussionmentioning
confidence: 69%
“…In this review, in one of the five studies examining woman sexual functions by using FSFI scale alone, it has been shown that sexual functions deteriorated in the first month postoperatively (12); and in one study it has been shown that sexual function did not change in an average of 3.15 (2.76-3.83) years postoperatively, while it has been shown to increase over time in all evaluations in other times (8,12,15,11,17). The increase of sexuality may be related to resolvement of the physical problms.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations